Effects of short-interval and long-interval swimming protocols on performance, aerobic adaptations, and technical parameters: A training study - Dalamitros, A. A.; Zafeiridis, A. S.; Toubekis, A. G.; Tsalis, G. A.; Pelarigo, J. G.; Manou, V.; Kellis, S. (The Journal of Strength and Conditioning Research, 2016)
This study compared 2-interval swimming training programs of different work interval durations, matched for total distance and exercise intensity, on swimming performance, aerobic adaptations, and technical parameters. Twenty-four former swimmers were equally divided to short-interval training group (INT50, 12-16 × 50 m with 15 seconds rest), long-interval training group (INT100, 6-8 × 100 m with 30 seconds rest), and a control group (CON). The 2 experimental groups followed the specified swimming training program for 8 weeks. Before and after training, swimming performance, technical parameters, and indices of aerobic adaptations were assessed. INT50 and INT100 improved swimming performance in 100 and 400-m tests and the maximal aerobic speed (p = 0.05); the performance in the 50-m swim did not change. Posttraining VO2max values were higher compared with pretraining values in both training groups (p = 0.05), whereas peak aerobic power output increased only in INT100 (p = 0.05). The 1-minute heart rate and blood lactate recovery values decreased after training in both groups (p < 0.01). Stroke length increased in 100 and 400-m swimming tests after training in both groups (p = 0.05); no changes were observed in stroke rate after training. Comparisons between groups on posttraining mean values, after adjusting for pretraining values, revealed no significant differences between INT50 and INT100 for all variables; however, all measures were improved vs. the respective values in the CON (p < 0.001-0.05). In conclusion, when matched for distance and exercise intensity, the short-interval (50 m) and long-interval (100 m) protocols confer analogous improvements in swimming performance, in stroke cycle parameters, and in indices of aerobic adaptations after 8 weeks of training.